Can tactile stimuli be subitised? An unresolved controversy within the literature on numerosity judgments. - Gallace, A; Tan, H; Spence, C (2008)
There is a growing interest in the question whether the phenomenon of subitising (fast and accurate detection of fewer than 4-5 stimuli presented simultaneously), widely thought to affect numerosity judgments in vision, can also affect the processing of tactile stimuli. In a recent study, in which multiple tactile stimuli were simultaneously presented across the body surface, Gallace et al (2006 Perception 35 247-266) concluded that tactile stimuli cannot be subitised. By contrast, Riggs et al (2006 Psychological Science 17 271 275), who presented tactile stimuli to participants' fingertips, came to precisely the opposite conclusion, arguing instead that subitising does occur in touch. Here, we re-analyse the data from both studies using more powerful statistical procedures. We show that Riggs et al's error data do not offer strong support for the subitising account and, what is more, Gallace et al's data are not entirely compatible with a linear model account of numerosity judgments in humans either. We then report an experiment in which we compare numerosity judgments for stimuli presented on the fingertips with those for stimuli presented on the rest of the body surface. The results show no major differences between the fingers and the rest of the body, and an absence of subitising in either condition. On the basis of these observations, we discuss whether the purported existence of subitisation in touch reflects a genuine cognitive phenomenon, or whether, instead, it may reflect a bias in the interpretation of the particular psychometric functions that happen to have been chosen by researchers to fit their data.